Upaya Meningkatkan Aktivitas dan Hasil Belajar Peserta Didik Kelas IV SD Negeri 14 Cakranegara Melalui Penerapan Pendekatan Cooperative Learning Tipe Jigsaw - I Ketut Nirta (Jurnal Paedagogy, 2019)
The purpose of this study was to determine the effectiveness of the application of the Jigsaw cooperative learning approach in an effort to improve the activities and learning outcomes of grade IV students at SD Negeri 14 Cakranegara. The benefits of this research are as study material and findings in the implementation of the learning process in the classroom and for teachers to improve competence in the learning process and for students to improve learning activities that have an impact on increasing student learning outcomes. This research uses a class action research method which is carried out in two cycles, each of which is a cycle of activities; planning, implementation, observation and reflection. The final results of the action in the second cycle showed that the results of teacher observation obtained an average score (4.43) and the results of student observations achieved an average score (4.33). While the results of an increase in student learning activities is an increase in student learning outcomes reaching an average value (87.15), meaning that the indicators of success (> 75.00) have been exceeded. Because the indicators of success have been proven, this research was declared successful and stopped in the second cycle.